PERAN KECERDASAN ADVERSITAS DAN KEMANDIRIAN MAHASISWI MELALUI KEGIATAN UBUDIAH DI PESANTREN TAKHASUS IIQ JAKARTA - Tsamrotul Faidah; Romlah Widayati (Qiro'ah : Jurnal Pendidikan Agama Islam, 2023)
This study aims to determine the role of student adversity intelligence through ubudiah activities and student independence through ubudiah activities at the Takhasus Islamic Boarding School IIQ Jakarta. This research method is a qualitative method. This type of research is descriptive research with a qualitative research approach. While the data collection techniques with interviews, observation and documentation. This research is different from other studies that have existed before. Because researching adversity intelligence and independence of students through ubudiah activities contained in the Takhasus Islamic boarding school IIQ Jakarta. Existing research on Advesity Intelligence and Independence has not yet been linked to ubudiah activity. The results of this study are the role of student adversity intelligence through Ubudiah Activities at the Takhasus IIQ Jakarta Islamic Boarding School able to restore the spirit of female students, help students stick to the principles they already have and not be influenced by others, help solve problems faced by female students, strengthen In addition, the role of student independence is to be able to improve student discipline, play a role in fostering confidence in female students' abilities, helping female students to be able to take responsibility responsible for himself and his duties in participating in ubudiah activities, helping female students control themselves, and giving lessons so as not to depend on others.